Origins of scientific economics - Letwin, William (London, 1963)
The popular notion that Adam Smith invented economics has always discomfited those historians of economic thought who, like all true historians, feel a strong urge to trace things back to their utmost beginnings. The work of discovering origins that predate the apparent original was begun soon after Smith's time by such of his followers as James Mill and J. R. McCulloch. Being inclined to view economic theory as a particularly elegant way of demonstrating the merits of laissez-faire, they concluded that whoever advocated free trade must be something of an economist, and they located several writers during the seventeenth and early eighteenth centuries who had advocated it so forcefully as to qualify them, in their eyes, as considerable economists. As economics became more elaborate and refined, interest in its history became more intense, and the historians slowly succeeded in proving that not only medieval churchmen, moralists and merchants, but even ancient philosophers had commented on economic mat ters. More recently still, some have penetrated beyond classical antiquity to find that ancient Chinese sages and Babylonian lawgivers made wise pronouncements on economic subjects. Having by now located the beginning of economics at the very beginnings of history, they rested confident of having achieved their calling's highest goals.
Keywords: Economics